N-Methyl-D-Aspartate Receptors Antagonist Prevents Secondary Ischemic Brain Injury Associated With Lipopolysaccharide-Induced Sepsis-Like State Presumably via Immunomodulatory Actions - Taheri, Golnar; Sardari, Maryam; Hermann, Dirk M.; Sepehri, Houri (Frontiers in Cellular Neuroscience, 2022)
Infection is a major reason for poor stroke outcomes, and sepsis is a major cause of stroke-elated deaths. We herein examined whether NMDA receptor blockade, which was reported to exert anti-inflammatory actions, protects against the deleterious consequences of lipopolysaccharide (LPS)-induced sepsis-like state in adult male NMRI mice exposed to transient intraluminal middle cerebral artery occlusion (MCAO). At 24 h post-ischemia, vehicle or Escherichia coli LPS (2 or 4 mg/kg) was intraperitoneally administered, whereas 30 min later vehicle or ketamine (10 mg/kg), which is a non-competitive NMDA receptor antagonist, was intraperitoneally applied. Delivery of LPS at a dosage of 4 mg/kg induced a sepsis-like state characterized by a rectal temperature reduction by ⁓4.0°C, increased neurological deficits in Clark score, cylinder and open-field tests, increased brain infarct volume and reduced neuronal survival in the previously ischemic tissue. Notably, additional treatment with ketamine (10 mg/kg) significantly attenuated the sepsis-associated rectal temperature reduction by ⁓1.5 ̊C, reduced neurological deficits, reduced infarct volume, and promoted neuronal survival. Ketamine alone did not influence infarct volume or neurological deficits. Real-time PCR data analysis showed that GFAP, CD86, CD206, IL-1β, and IL-10 mRNA levels were significantly increased in ischemic brains of LPS-treated compared with vehicle-treated mice. Additional treatment with ketamine significantly decreased IL-1β and IL-10, but not GFAP, CD86, and CD206 mRNA levels. Our data show that ketamine at a dose that on its own does not confer neuroprotection reverses the adverse effects of LPS-induced sepsis-like state post-ischemia, presumably via immunomodulatory actions.